Protest at Army Recruiting Office Against U.S. Military in Central America - Watkins, Howard::::::::: (1988)
Banners "Vietnam 1968 Nicaragua 1988." "US OUT OF CENTRAL AMERICA NOW," and "THE DECISION IS NOW." 1920 Mariposa Mall, Fresno;